Conceptual application of digital twins to meet ESG targets in the mining industry - Cranford, Rachel (Frontiers in Industrial Engineering, 2023)
Environmental, social, and governance (ESG) focus continues to gain traction in the mining industry through publicly made policies, promises, and commitments. In 2022, both ESG and technological investments were identified in the top trends by Deloitte and in the top risks and opportunities by Ernst and Young. As the first step in the value chain, the mining industry sets the foundation for most industries in meeting their ESG targets. Beyond providing sustainable materials, the mining industry is required to produce the critical minerals needed for the creation of sustainable technologies. With an ongoing debate on how ESG factors should be measured and inconsistent reporting between mining companies, there remains a gap in consistent and auditable progress in ESG reporting. This study evaluates the application of a digital twin technology to bridge the gap in ESG reporting. By examining the use of digital twin technology through thirty case studies and theoretical applications across industries that share commonalities with mining, this study analyzes the opportunity to apply the technology to the mining industry. The research found that digital twin technology can be applied across all mining project phases and can provide added value to improve multiple ESG factors and measure them. Though the research identifies that there are benefits from the application of digital twin technology to all project phases, and across all three ESG dimensions, there remains challenges to implementation. Successful implementation of digital twin technology will require the right people with the right capabilities. Though suggested that the mining industry should let other industries stabilize the digital twin market due to their history and substantial investment in data systems, it is arguable through literature, case studies and leading mining companies’ investments in precursor technologies to digital twins, that solutions are available and scalable, and the time to wait is over.